PENGGUNAAN PEMETAAN KONFORMAL PADA MASALAH INVERS - Saleh, Khairul
Abstract: Some two-dimensional geometrical inverse problems are solved exactly through conformal mapping theory. Some illustrative examples show the applicability of the results. An algorithm suitable for numerical applications is also given.